Masked Speech Recognition in School-Age Children - Leibold, Lori J.; Buss, Emily (Frontiers in Psychology, 2019)
Children who are typically developing often struggle to hear and understand speech in the presence of competing background sounds, particularly when the background sounds are also speech. For example, in many cases young school-age children require an additional 5-10 dB signal-to-noise ratio relative to adults to achieve the same word or sentence recognition performance as adults in the presence of two streams of competing speech. Moreover, adult-like performance is not observed until adolescence. Despite ample converging evidence that children are more susceptible to auditory masking than adults, the field lacks a comprehensive model that accounts for the development of masked speech recognition. This review provides a synthesis of the literature on the typical development of masked speech recognition. Age-related changes in the ability to recognize phonemes, words, or sentences in the presence of competing background sounds will be discussed by considering (1) how masking sounds influence the sensory encoding of target speech; (2) differences in the time course of development for speech-in-noise versus speech-in-speech recognition; and (3) the central auditory and cognitive processes required to separate and attend to target speech when multiple people are speaking at the same time.